The Laboratorium: Nineteenth-Century French Studies in the Anglophone Sphere (Part II). (2nd January 2023) - Harrow, Susan
ABSTRACT: This is the second instalment of a two-part thematic review of nineteenth-century French research in the Anglophone sphere. The review sets aside the standard sub-disciplinary categories in order to envision a laboratorium, a space of multiple confluent and contiguous lines of exploratory work. In this space, more fluid thematic connections surface between projects irrespective of their focus, their methodology, or their scale, revealing some of the major transversal routes of research across the recent past and the present, and, speculatively, into the future. The two-part review explores biography / body / earth / emotion / experiment / movement / thing.